Gender differences in knee kinematics during landing from volleyball block jumps - Hughes, G.; Watkins, J.; Owen, N.; Lewis, M. (Journal of Human Movement Studies, 2007)
The aims of the present study were to investigate the effects of gender on frontal and sagittal plane knee kinematics in university volleyball players when performing opposed block jump landings. 6 female and 6 male university volleyball players performed volleyball block jumps under opposed conditions. Knee flexion/extension and knee valgus/ varus angles and angular velocities were determined during landing. Knee flexion at ground contact was significantly smaller in females than males. Maximum knee flexion and range of motion of knee flexion was significantly greater in females. In the frontal plane, there was no significant difference between males and females in knee valgus angle on ground contact, but females displayed significantly greater maximum valgus angle and range of motion than males. There was a significant difference in maximum valgus and range of motion between the dominant and non-dominant legs in females, but not in males. Angular velocity of the knees in both frontal and sagittal planes was significantly greater in females than males in the passive phase of landing, but not in the active phase. The gender differences in lower limb alignments when in normal upright standing position do not totally account for the gender differences in landing kinematics. The results appear to indicate less dynamic stability of the knee during landing in females compared to males which may be a contributory factor in the reported greater incidence of anterior cruciate ligament (ACL) injury in females.